2000
DOI: 10.1152/jappl.2000.89.5.2065
|View full text |Cite
|
Sign up to set email alerts
|

Response of arterial smooth muscle to length perturbation

Abstract: The ability of arterial smooth muscle to generate tension is influenced by muscle length. An unsettled question is whether the length-tension relationship is a simple reflection of the contractile filament overlap, as it is in skeletal muscle. There are several factors that could potentially affect tension generation in arterial smooth muscle; these include stretch-induced myogenic response and length-oscillation-induced disruption of the contractile filament organization. In this study, in which rabbit caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 32 publications
(47 reference statements)
5
40
0
Order By: Relevance
“…Because muscle cell active tension is due to the transmission through cytoskeletal adhesion junctions of tension generated by actomyosin cross bridges, the proposed mechanisms for length adaptation of active tension include changes in actin and myosin polymerization leading to addition and subtraction of sarcomeres, and sarcomere and cytoskeletal adhesion junction reorganization (13,16,17,25). Although the most extensive work on length adaptation of active tension has been done on airway smooth muscle (12), there is also evidence of length adaptation of active tension in certain arteries (40,51), rabbit bladder (45), and cat ileum (3).…”
mentioning
confidence: 99%
“…Because muscle cell active tension is due to the transmission through cytoskeletal adhesion junctions of tension generated by actomyosin cross bridges, the proposed mechanisms for length adaptation of active tension include changes in actin and myosin polymerization leading to addition and subtraction of sarcomeres, and sarcomere and cytoskeletal adhesion junction reorganization (13,16,17,25). Although the most extensive work on length adaptation of active tension has been done on airway smooth muscle (12), there is also evidence of length adaptation of active tension in certain arteries (40,51), rabbit bladder (45), and cat ileum (3).…”
mentioning
confidence: 99%
“…For example, it is known that stretch could induce a contraction of smooth muscle referred to as myogenic response. The stretch-induced myogenic response is a recognized phenomenon in vascular smooth muscle (9,27). Induction of myogenic response has also been shown in guinea pig ASM, and this response could be abolished by inhibiting prostanoid release with indomethacin (11).…”
mentioning
confidence: 99%
“…The half-time for isometric stress recovery varies depending on the smooth muscle type used. Wang et al (2001) reported a half-time of 3-5 mins (depending on the length the specimen was adapted to) for rabbit airway smooth muscle while it was approximately 7 mins for rabbit carotid arteries, see Seow (2000). Comparing with Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, length adaptation operates on a time scale of minutes to hours (Pratusevich et al, 1995;Seow, 2000;Syyong et al, 2008) while maximum smooth muscle contraction can be achieved within seconds. This implies thatṅ ≈ 0 compared to the strain rate so thaṫ…”
Section: Kinematicsmentioning
confidence: 99%